Do Volatility Shocks Matter More Than Policy Uncertainty? A Behavioral Analysis of Bank Equity Returns - VİGA, ŞABAN ONUR (Finance : International Journal of Management Finance, 2024)
This study investigates the relationship between global uncertainty indices and bank stock returns through the lens of behavioral finance. Using monthly data from January 2010 to December 2024, the analysis incorporates three regional banking indices—S&P 500 Bank Index (USA), MSCI World Banks Index (Global), and BIST XBANK Index (Türkiye)—and two prominent uncertainty indicators: the Global Economic Policy Uncertainty Index (GEPU) and the CBOE Volatility Index (VIX). While GEPU captures structural macro-level uncertainty through text-based analytics, VIX reflects short-term market sentiment based on option-implied volatility.  A series of econometric methods—including Augmented Dickey-Fuller (ADF) tests, Pearson correlation, Granger causality, vector autoregression (VAR), and impulse response functions (IRF)—were employed to assess the dynamic interactions between uncertainty shocks and bank equity returns. The findings reveal that VIX changes have statistically significant short-term negative effects on banking sector returns in all three markets, with the strongest reactions observed in the Turkish banking sector. Conversely, GEPU changes do not exhibit consistent causal or dynamic effects. These results suggest that market-based uncertainty (volatility shocks) is more influential than policy-related uncertainty in shaping short-term investor behavior and bank equity pricing. The study contributes to the literature by providing a multi-market behavioral assessment of uncertainty-return linkages, highlighting the differentiated impact of sentiment-based versus structural uncertainty measures across emerging and developed financial systems